A Qualitative Evaluation of a Life Skill Training Program in Physical Education - Kolovelonis Αθανάσιος; Goudas Μάριος; Dimitriou Ελένη; Hassandra Μαρία (Inquiries in Physical Education and Sport, 2010)
The aim of the study was to examine the effectiveness of a life skills training program in a physical education setting, using a qualitative approach. Participants were 76 seventh grade students. The life skills program included goal setting, positive thinking and self-talk and consisted of 8 lessons which were implemented in connection with a physical fitness program. Sixteen interviews from 8 boys and 8 girls were conducted after the end of the intervention. Data were coded through thematic analysis (Boyatzis, 1998) in the following dimensions: usefulness, satisfaction, function, transfer, and comprehension. Results showed that students comprehended the teaching of the life skills program and found it enjoyable, interesting, useful and beneficial. In addition, students reported that they used the life skills, not only during physical education, but also in other subjects as well as in circumstances out of school. In conclusion, the life skills training program was effective and can contribute to the achievement of physical education goals.